Ixodes ricinus as potential vector for Usutu virus. - Julian W Bakker; Emmanuelle Münger; Helen J Esser; Reina S Sikkema; Willem F de Boer; Hein Sprong; Chantal B E M Reusken; Ankje de Vries; Robert Kohl; Anne van der Linden; Arjan Stroo; Henk van der Jeugd; et al. (Public Library of Science (PLoS), 2024)
Usutu virus (USUV) is an emerging flavivirus that is maintained in an enzootic cycle with mosquitoes as vectors and birds as amplifying hosts. In Europe, the virus has caused mass mortality of wild birds, mainly among Common Blackbird (Turdus merula) populations. While mosquitoes are the primary vectors for USUV, Common Blackbirds and other avian species are exposed to other arthropod ectoparasites, such as ticks. It is unknown, however, if ticks can maintain and transmit USUV. We addressed this question using in vitro and in vivo experiments and field collected data. USUV replicated in IRE/CTVM19 Ixodes ricinus tick cells and in injected ticks. Moreover, I. ricinus nymphs acquired the virus via artificial membrane blood-feeding and maintained the virus for at least 70 days. Transstadial transmission of USUV from nymphs to adults was confirmed in 4.9% of the ticks. USUV disseminated from the midgut to the haemocoel, and was transmitted via the saliva of the tick during artificial membrane blood-feeding. We further explored the role of ticks by monitoring USUV in questing ticks and in ticks feeding on wild birds in the Netherlands between 2016 and 2019. In total, 622 wild birds and the Ixodes ticks they carried were tested for USUV RNA. Of these birds, 48 (7.7%) carried USUV-positive ticks. The presence of negative-sense USUV RNA in ticks, as confirmed via small RNA-sequencing, showed active virus replication. In contrast, we did not detect USUV in 15,381 questing ticks collected in 2017 and 2019. We conclude that I. ricinus can be infected with USUV and can transstadially and horizontally transmit USUV. However, in comparison to mosquito-borne transmission, the role of I. ricinus ticks in the epidemiology of USUV is expected to be minor.